The legend of St. Brendan : a comparative study of the Latin and Anglo-Norman versions - Mackley, J. S. (Jude S.) (Northern world ;, 2008)
Presenting a comparative study of the Latin and Anglo-Norman Versions of the Voyage of Brendan, this work offers an insight into the way that fantastic imagery was used to discuss sensitive theological issues in one of the most popular medieval narratives. It also addresses issues raised with respect to theological parallels.